2018
DOI: 10.4103/ijo.ijo_344_18
|View full text |Cite
|
Sign up to set email alerts
|

Angle closure glaucoma in rural and urban populations in eastern India—The Hooghly River Glaucoma Study

Abstract: Purpose:To estimate the prevalence, features, and associations of primary angle closure disease (PACD) in rural and urban populations from West Bengal in eastern India.Methods:This was a population-based cross-sectional study with two arms, rural and urban. The rural study area consisted of 28 contiguous villages from 13 gram panchayats in Balagarh Police Station, with rural base hospital at Dhobapara, Balagarh Police Station, in the village Kuliapara of Hooghly district. A tertiary eye hospital in central Kol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…However, research in India has shown that the risk of developing closed glaucoma is higher in rural populations, while those patients with DM may have a higher risk of developing glaucoma. No statistical relationship has been established between air pollution and blood pressure disorders [ 32 ]. In urban areas, the open-angle glaucoma had a high prevalence due to the higher prevalence of myopia in these areas [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, research in India has shown that the risk of developing closed glaucoma is higher in rural populations, while those patients with DM may have a higher risk of developing glaucoma. No statistical relationship has been established between air pollution and blood pressure disorders [ 32 ]. In urban areas, the open-angle glaucoma had a high prevalence due to the higher prevalence of myopia in these areas [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“… 1 PACG is predominantly asymptomatic in the Asian population 2 and >90% of the cases go undiagnosed, making it difficult to study the true prevalence. 3 The relative lack of health-care resources in some of these countries is another factor contributing to its underestimation.…”
Section: Introductionmentioning
confidence: 99%
“… 4 Kurita et al showed that central AC depth (ACD) is a better predictor of primary angle closure than AC angle or AC volume. 5 Multiple studies have confirmed central ACD as a good surrogate marker for development of angle-closure disease, 3–5 making it an ideal parameter that can be used as a screening tool.…”
Section: Introductionmentioning
confidence: 99%
“…7 There are huge variations in the strength of association of different retrobulbar blood flow parameters with type, severity of glaucoma 5,[8][9][10] , with only limited number available in Indian population. 11,12…”
Section: Introductionmentioning
confidence: 99%